Development and Validation of a Novel Prognostic Nomogram for CD5-Positive Diffuse Large B-Cell Lymphoma: A Retrospective Multicenter Study in China - Shen, Ziyuan; Wang, Ling; Zhang, Bingpei; Li, Tianci; Li, Dashan; He, Chenlu; Xue, Yuhao; Wang, Ying; Li, Bingzong; Liu, Qinhua; Zhang, Hao; Gu, Weiying; et al. (Frontiers in Oncology, 2021)
Background: CD5 positive diffuse large B cell lymphoma (CD5+ DLBCL) is a highly heterogeneous DLBCL subtype with invasive clinical features and poor prognosis. Current clinical-variables based prognostic systems for DLBCL are hard to accurately stratify the prognosis of CD5+ DLBCL. Methods: A total of 195 CD5+ DLBCL patients were retrospectively recruited from 9 centers in Huaihai Lymphoma Working Group. MaxStat analysis was used to identify optimal cut-off points for continuous variables; Univariable and multivariable Cox analyses were used for variables selection; Kaplan‐Meier curve was used to analyze the value of variables on prognosis; C-index, brier score and decision curve analysis were measured for predicting model performance. Results: The derivation and validation cohorts were consisted of 131 and 64 patients. Of the whole cohort, median age at diagnosis was 61 years, of whom 100 (51.28%) were males and the 5‐year overall survival rate was 42.1%. MYC, BCL-2 and the coexpression of MYC/BCL-2 could distinguish the survival of CD5+ DLBCL. Multivariable analysis showed that age, IPI, red blood cell count, neutrophil count, MYC expression and hepatosplenomegaly were independent predictors and the prognostic nomogram was developed. The C‐index of the nomogram was 0.809 in the derivation and 0.770 in the validation cohort. Decision curve analysis proved that compared with IPI, the specific nomogram showed a better identification in CD5+ DLBCL. Conclusion: The proposed nomogram provided a valuable tool for prognosis prediction in patients with CD5+ DLBCL.